Changes of oral health motivation and knowledge following the implementation of the android-based quitee educational application among children aged 8–11 years: a pre-experimental study - Aldilawati, Sari; Pratiwi, Rini; Adawiyyah, Nurul Afni (Padjadjaran Journal of Dentistry, 2026)
Introduction: Motivation and oral health knowledge among elementary school children remain suboptimal. Interactive digital educational applications, such as the Android-Based Quitee Educational Application, have been developed as engaging learning tools for oral health through visuals, animations, and game-based elements that are appropriate for children’s characteristics. This study aimed to evaluate changes in oral health motivation and knowledge following the implementation of the Android-Based Quitee Educational Application among children aged 8–11 years. Methods: This study employed a pre-experimental one-group pretest-posttest time-series design. The sample size was calculated using the Slovin formula, resulting in 126 participants selected through proportionate stratified random sampling from SD Negeri Tamamaung 1 Makassar. Oral health motivation and knowledge were measured before the intervention and at three post-intervention time points following the implementation of the Android-Based Quitee Educational Application. Data were analyzed using the Friedman test, followed by post hoc Wilcoxon signed-rank tests. Results: Oral health motivation and knowledge scores increased across all post-intervention assessments compared with baseline measurements. The median motivation score increased from 14.0 at pretest to 19.0 at the third posttest, whereas the median knowledge score increased from 9.0 to 12.0. All pairwise comparisons were statistically significant (p<0.001), with Wilcoxon effect sizes indicating large effects for motivation (r=0.63–0.87) and moderate-to-large effects for knowledge (r=0.33–0.84), demonstrating the magnitude of the observed improvements.   Conclusion: The implementation of the Android-Based Quitee Educational Application was associated with significant improvements in oral health motivation and knowledge among elementary school children. However, the findings should be interpreted cautiously due to the absence of a control group.